Short communication: psychrotrophic microorganism count in raw milk samples preserved with azidiol® - Felipus, Nadine Cristina; Thaler Neto, André; Bajaluk, Sergio Antonio Bogdano; Voges, Joana Gerent; Knob, Deise Aline (Acta Scientiarum. Animal Sciences, 2022)
The study aimed to evaluate the use of the azidiol® preservative for psychrotrophic microorganism count (PMC) in cooled raw milk. Two studies were carried out, one under controlled conditions (experiment 1) and the other under field conditions (experiment 2), in which samples of raw milk were taken with and without the use of the azidiol® preservative and analyzed at predefined times (0, 6, 12 and 24 hours - experiment 1) and at varying times (experiment 2). Analysis of variance and regression analysis using SAS were applied for data statistical analysis. Milk samples without azidiol® showed higher PMC with increasing time between sampling and analysis, while in samples preserved with azidiol®, this count remained constant. Samples of cooled raw milk intended for PMC should be collected in flasks containing the azidiol® preservative.